1998
DOI: 10.1002/clc.4960210713
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous manifestation of acute myocardial infarction and nephrotic syndrome

Abstract: Summary: This report describes the simultaneous manifestation of ischemic heart disease and nephrotic syndrome in a 37-year-old woman presenting with acute anterior myocardial infarction. Symptoms of nephrotic syndrome, such as facial and peripheral edema accompanied by proteinuria and hyperlipidemia, and onset of severe retrostemal pain developed within 24 h. Coronary angiography revealed a complete thrombotic occlusion of the proximal portion of the left anterior descending artery with no evidence of arterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
0
10
0
3
Order By: Relevance
“…Taylor [13] reported a rare occurrence of myocardial infarction in a rural black African 44-year-old female. Recently, other authors have reported acute myocardial infarction secondary to thrombotic complications in young adults with nephrotic syndrome [14,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Taylor [13] reported a rare occurrence of myocardial infarction in a rural black African 44-year-old female. Recently, other authors have reported acute myocardial infarction secondary to thrombotic complications in young adults with nephrotic syndrome [14,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Coronary thrombosis can be seen in hypercoagulable state, as in nephrotic syndrome [3], antiphospholipid syndrome [4], deficiencies of protein C, protein S and antithrombin III [5,6]. Renal involvement associated with nephritic syndrome may result in hypercoagulability, thus leading to AMI [3,7]. There are case reports and some small-sized series available that address development of AMI in young patients with SLE below 35 year [8].…”
Section: Discussionmentioning
confidence: 99%
“…This can be a significant factor in the development of arterial thrombus since arterial thrombi are mainly composed of platelets as compared to venous thrombi, which are predominantly formed from fibrin and red cells (Fahal et al . 1994; Meyer et al 1998). Increased blood viscosity secondary to haemoconcen‐tration due to diuretic use and high fibrinogen concentration can also contribute towards the thrombotic tendencies in nephrotic patients (Fahal et al .…”
Section: Discussionmentioning
confidence: 99%
“…The first report of MI complicating NS was published by Berlyne & Mallick (1969). Since then few case reports describing MI in young patients with longstanding NS and simultaneous presentation of MI and NS have also been published (Meyer et al 1998; Osula et al . 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation